Species diversity in the marine microturbellarian Astrotorhynchus bifidus sensu lato (Platyhelminthes: Rhabdocoela) from the Northeast Pacific Ocean - Van Steenkiste, N. W.; Herbert, E. R.; Leander, B. S. (Molecular Phylogenetics and Evolution, 2018)
Increasing evidence suggests that many widespread species of meiofauna are in fact regional complexes of (pseudo-)cryptic species. This knowledge has challenged the ‘Everything is Everywhere’ hypothesis and also partly explains the meiofauna paradox of widespread nominal species with limited dispersal abilities. Here, we investigated species diversity within the marine microturbellarian Astrotorhynchus bifidus sensu lato in the Northeast Pacific Ocean. We used a multiple-evidence approach combining multi-gene (18S, 28S, COI) phylogenetic analyses, several single-gene and multi-gene species delimitation methods, haplotype networks and conventional taxonomy to designate Primary Species Hypotheses (PSHs). This included the development of rhabdocoel-specific COI barcode primers, which also have the potential to aid in species identification and delimitation in other rhabdocoels. Secondary Species Hypotheses (SSHs) corresponding to morphospecies and pseudo-cryptic species were then proposed based on the minimum consensus of different PSHs. Our results showed that (a) there are at least five species in the A. bifidus complex in the Northeast Pacific Ocean, four of which can be diagnosed based on stylet morphology, (b) the A. bifidus complex is a mixture of sympatric and allopatric species with regional and/or subglobal distributions, (c) sympatry occurs on local (sample sites), regional (Northeastern Pacific) and subglobal (Northern Atlantic, Arctic, Northeastern Pacific) scales. Mechanisms for this co-occurrence are still poorly understood, but we hypothesize they could include habitat differentiation (spatial and/or seasonal) and life history characteristics such as sexual selection and dispersal abilities. Our results also suggest the need for improved sampling and exploration of molecular markers to accurately map gene flow and broaden our understanding of species diversity and distribution of microturbellarians in particular and meiofauna in general.